Tableau Desktop pocket reference : essential features, syntax, and data visualizations - Sleeper, Ryan (O'Reilly Media, Inc., 2021)
In a crowded field of data visualization and analytics tools, Tableau Desktop has emerged as the clear leader. This is partly due to its ease of use, but once you dive into Tableau's extensive feature set, you'll understand just how powerful and flexible this software can be for your business. With this handy pocket reference, author Ryan Sleeper (Practical Tableau and Innovative Tableau) shows you how to translate the vast amounts of data you've collected into useful information. Tableau has done an amazing job of making valuable insights accessible to analysts and executives who would otherwise need to rely on IT. This book quickly guides you through Tableau Desktop's learning curve. You'll learn: How to shape data for use with Tableau Desktop How to create the most effective data visualizations Core concepts including discrete versus continuous Must-know technical features including filters, parameters, and sets Key syntax for creating the most useful analyses How to bring it all together with dashboards And more.